2021
DOI: 10.21203/rs.3.rs-154054/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards Safer and More Sustainable Systems for Monitoring Exophagic Vectors of Malaria in Western Kenya

Abstract: Introduction. Longitudinal monitoring of outdoor-biting malaria vector populations is becoming increasingly important in understanding the dynamics of residual malaria transmission. However, the human landing catch (HLC), the gold standard for measuring human biting rates indoors and outdoors, is costly and raises ethical concerns related to increased risk of infective bites among collectors. Consequently, routine data on outdoor-feeding mosquito populations are usually limited due to the lack of a scalable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The largescale implementation of IRS contributed substantially to the elimination of malaria from 37 countries during the Global Malaria Elimination Campaign (1955)(1956)(1957)(1958)(1959)(1960)(1961)(1962)(1963)(1964)(1965)(1966)(1967)(1968)(1969) [1]. Following this success, IRS was expanded to malaria endemic countries in the African continent resulting in successful malaria control in diverse endemic settings over the past decades [2][3][4][5][6]. Modelling has indicated that the sustained deployment of IRS in high endemic settings was a major contributing factor to the substantial reductions in malaria burden observed between 2000 and 2015 [7].…”
Section: Introductionmentioning
confidence: 99%
“…The largescale implementation of IRS contributed substantially to the elimination of malaria from 37 countries during the Global Malaria Elimination Campaign (1955)(1956)(1957)(1958)(1959)(1960)(1961)(1962)(1963)(1964)(1965)(1966)(1967)(1968)(1969) [1]. Following this success, IRS was expanded to malaria endemic countries in the African continent resulting in successful malaria control in diverse endemic settings over the past decades [2][3][4][5][6]. Modelling has indicated that the sustained deployment of IRS in high endemic settings was a major contributing factor to the substantial reductions in malaria burden observed between 2000 and 2015 [7].…”
Section: Introductionmentioning
confidence: 99%